Trophic ecology and spatial behaviour of wolf (Canis lupus) in an Appennine area - BASSI, ELENA (Università degli studi di Sassari, 2014)
Nowadays the Italian wolf (Canis lupus) is expanding its range and increasing in numbers, nevertheless it is still a vulnerable species.In this work, we have focused on the wolf feeding and spatial behavior, in a region of Northern Apennine.First, we investigated the relation between wolf and red fox (Vulpes vulpes), assessing the extent of their trophic niche overlap. Our findings suggest a very limited trophic competition between them.Moreover, we analyzed the functional response of wolf to changes in prey availability, and the impact of wolf predation and hunting harvest on ungulate populations.Wild boar (Sus scrofa) was the main and selected prey species for wolves. Moreover, the proportion of roe deer (Capreolus capreolus) in wolf diet peaked when boar densities were low, resulting in a functional response dependent on the main prey density fluctuations. Furthermore, even if wolves and hunters focused on targets with different reproductive potential in the population, their combined impact did not exceed the annual recruitment, and thus did not result to limit ungulates population growth.Finally, analyzing the variables involved in the choice of rendezvous sites locations, we found rendezvous sites typically inside protected areas, and usually distant from human settlements. Over recent years, rendezvous sites have occurred closer to urban areas, thus, our projections of suitability of sites can help planning to minimize possible wolf-human conflicts.